(ARTICLE RETRACTED) Diagnostic value of VIA comparing with conventional Pap smear in the detection of colposcopic biopsy proved CIN (Bangladesh Journal of Medical Science, 2011)
This article has been retracted because it has already been published in the Nepal Journal of Obstetrics and Gynaecology Vol.6(1) 2011 pp.7-12. http://www.nepjol.info/index.php/NJOG/article/view/5245